Growth characteristics of electrical trees in epoxy resin at cryogenic temperatures. (April 2019) - Wang, Y.G.; Ma, J.H.; Huang, R.J.; Luo, L.M.; Liang, Y.Q.; Shen, F.Z.; Li, J.; Xu, D.; Zhang, H.; Zhang, C.; Li, L.F.
Abstract: The electrical tree aging problem of epoxy resin has serious impacts on the insulation structure of superconducting magnet. It is necessary to investigate the growth characteristics of electrical trees in epoxy resin at cryogenic temperatures. The experimental system with a microscopic observation apparatus and a cryostat filled with the liquid nitrogen (LN2 ) was set up. Each group of samples was tested at a range of AC voltages from 8 kV rms to 20 kV rms and the partial discharge (PD) experiments were carried out at 298 K and 77 K. The results showed that the generation of electrical trees was resisted strongly at cryogenic temperatures. The growth of electrical trees was slower and the tree inception voltage increased obviously at cryogenic temperatures. Meanwhile, the degree of damage to materials caused by partial discharge at cryogenic temperatures was even more severe than that at room temperature.